Pemberdayaan Usaha Mikro Kecil Aksesoris Aquarium Desa Tamanharjo Singosari Kabupaten Malang - Lutviana, Rizky; Kurniawati, Maris (Jurnal Pemberdayaan Masyarakat, 2019)
This community service program aimed at empowering H-Fish aquarium Assesories small business to become independent and developed. A business may be considered as developed if it meets criteria such as increasing revenue, increasing product variation, efficient production, good packaging, and good management system that meets standard. In order to achieve that goal, the researcher gave sequencial trainings including training in operating and maintenance the machine production, training in packaging product and label design, training business management that meets standard and training in product variation. Besides, the researcher also helped to improve product marketing including renovating production side and building showroom to display the product to attract potential buyers. The results of this community service were increasing revenue since the product variation is increasing and the packaging was also improved to be more attractive. H-Fish Aquarium Assesories developed well because of efficient production, good business management, and wider marketing.